2019
DOI: 10.1111/bjso.12350
|View full text |Cite
|
Sign up to set email alerts
|

Whites’ racial identity centrality and social dominance orientation are interactively associated with far‐right extremism

Abstract: This paper presents evidence from five studies (total White N = 7,209) that White American’s racial identity centrality is related to self‐reported levels of far‐right extremism. Furthermore, evidence from two of the studies shows that social dominance orientation (SDO) is another robust predictor of far‐right extremism. Results also show that SDO can moderate the relationship between White identity and extremism such that the association is stronger for Whites with a higher level of SDO. Therefore, evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…As discussed above, the results overall suggest that ideology can play an important role after all, and to some extent, it plays a more powerful role than party identity. These results are consistent with recent findings that (in)egalitarian ideology seems to be a stronger predictor of extremisms on racial or racialized topics than racial identity (Bai, 2020). However, what is it that makes values so special relative to their group identity?…”
Section: Why Does Ideology Play a More Important Role?supporting
confidence: 92%
“…As discussed above, the results overall suggest that ideology can play an important role after all, and to some extent, it plays a more powerful role than party identity. These results are consistent with recent findings that (in)egalitarian ideology seems to be a stronger predictor of extremisms on racial or racialized topics than racial identity (Bai, 2020). However, what is it that makes values so special relative to their group identity?…”
Section: Why Does Ideology Play a More Important Role?supporting
confidence: 92%
“…We argue that two important political-psychological predispositions that may be associated with belief in COVID-19 origin theories are right-wing authoritarianism (RWA) and social dominance orientation (SDO). Both RWA and SDO emerged from research investigating different individual-level factors that explain prejudice and are thought to represent two types of right-wing personalities (Altemeyer, 1981;Diaz-Veizades et al, 1995;Duckitt, 2001;Sibley et al, 2006;Wilson and Sibley, 2013). In the Dual Process Motivational Model, for example, Duckitt (2001) theorised that two sets of motivational schemas, threat-control and competition-dominance, are the foundations of RWA and SDO, respectively, and that these dimensions were responsible for distinct forms of prejudice.…”
Section: A Motivational Model Of Belief In Conspiracy Theoriesmentioning
confidence: 99%
“…At the individual level, researchers have shown that far-right extremism is predicted by being unemployed, hostility toward immigration (Lubbers, Gijsberts, & Scheepers, 2002), and a belief in the in-group's superiority (Doosje et al, 2012). Evidence also suggests that social dominance orientation, identification with the White ingroup, and their interaction also predict far-right extremism in the United States (Bai, 2020).…”
Section: Demographic Shift Threats and Far-right Extremismmentioning
confidence: 99%